IMPLEMENTASI NILAI-NILAI MULTIKULTURAL DI SEKOLAH DASAR - Kurotul Aeni; Tri Astuti (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
The research aims to describe and analyze the implementation of multicultural values in SD Global Inbyra School (GIS) and SD Pelita Harapan Bangsa (PHB).The research method used is the naturalistic inquiry case study approach. Retrieval of data using observations, interviews, and documentation. The validity of the data is done by confirming the results of observations, interviews, documentation. Data credibility testing is done by extending observations, increasing persistence, triangulation of data, member checks, and references. Data analysis uses the interactive model of Miles and Huberman.The results showed that the implementation of multicultural values in GIS and PHB as follows 1) was carried out in an integrated manner through intracuricular and extracurricular activities; 2) The role is very dominant shown by the principal, teachers, and students have the same understanding and positive influence in the development of multicultural values as an effort to build the character of students. The differences are (1) in SD GIS: (a) the application of English as the language of instruction makes students familiar with the term English in relation to the use of technology; confident in interacting with strangers / foreigners; (b) implementation of multicultural values through character building subjects; (c) the existence of a dual curriculum program, namely the integration and integration of national and international curricula (cambridge) that balances student potential, opportunities, ethnic background, religious beliefs and ideals to create individuals to socialize with different cultures.